Antioxidant and antibacterial activity of Apis laboriosa honey against Salmonella enterica serovar Typhimurium - Tan, Weihua; Tian, Yuanyuan; Zhang, Qingya; Miao, Siwei; Wu, Wenrong; Miao, Xiaoqing; Kuang, Haiou; Yang, Wenchao (Frontiers in Nutrition, 2023)
Salmonella enterica serovar Typhimurium (S. Typhimurium) is a common food-borne pathogen that commonly causes gastroenteritis in humans and animals. Apis laboriosa honey (ALH) harvested in China has significant antibacterial activity against Staphylococcus aureus, Escherichia coli, and Bacillus subtilis. We hypothesize that ALH has antibacterial activity against S. Typhimurium. The physicochemical parameters, minimum inhibitory and bactericidal concentrations (MIC and MBC) and the possible mechanism were determined. The results showed that there were significantly different physicochemical parameters, including 73 phenolic compounds, among ALH samples harvested at different times and from different regions. Their antioxidant activity was affected by their components, especially total phenol and flavonoid contents (TPC, TFC), which had a high correlation with antioxidant activities except for the O2- assay. The MIC and MBC of ALH against S. Typhimurium were 20–30% and 25–40%, respectively, which were close to those of UMF5+ manuka honey. The proteomic experiment revealed the possible antibacterial mechanism of ALH1 at IC50 (2.97%, w/v), whose antioxidant activity reduced the bacterial reduction reaction and energy supply, mainly by inhibiting the citrate cycle (TCA cycle), amino acid metabolism pathways and enhancing the glycolysis pathway. The results provide a theoretical basis for the development of bacteriostatic agents and application of ALH.